Effect of precursor structures on the electrochemical performance of Ni-rich LiNi0.88Co0.12O2 cathode materials. (20th April 2018) - Li, Gang; Qi, Lin; Xiao, Peng; Yu, Yongli; Chen, Xu; Yang, Wensheng
Abstract: The structure design and synthesis of precursors is a key factor to improve the electrochemical properties of Ni-rich cathode materials. However, for the core-shell precursors, the structural evolution in the lithiated process and its effect on the structure and electrochemical properties of the final products has not been clearly elucidated. Herein, three LiNi0.88 Co0.12 O2 materials are synthesized from three different structured precursors, namely the completely coated 0.88Ni(OH)2 @0.12Co(OH)2, the semi-coated & semi-doped 0.94Ni0.936 Co0.064 (OH)2 @0.06Co(OH)2, and the completely doped Ni0.88 Co0.12 (OH)2, respectively. Unexpectedly, the core-shell structures of the completely coated and semi-coated & semi-doped precursors disappears, and the radial concentration distributions of Ni and Co are almost uniform in spherical LiNi0.88 Co0.12 O2 particles obtained by sintering with LiOH·H2 O, no matter the precursor is coating type or doping type. Even so, the LiNi0.88 Co0.12 O2 material synthesized from the 0.88Ni(OH)2 @0.12Co(OH)2 precursor still has the best electrochemical properties with the specific discharge capacity of 215 mAh g −1 at 0.1 C (20 mA g −1 ) and the capacity retention of 88.6% after 100 cycles. The reason is that the cobalt hydroxide coating layer on the surface of precursor acts as a barrier to decrease the diffusing rate of lithium ions into the core material, which leaves enough time to make Ni 2+ be oxidized to Ni 3+ as many as possible. This work not only synthesizes a high-performance LiNi0.88 Co0.12 O2 material, but also clearly reveals the reaction mechanism and provides valuable references for synthesizing high-performance LiNi1- x- y Co x Mny O2 (NCM) or LiNi0.8 Co0.15 Al0.05 O2 (NCA) materials.